Penentuan Nilai Porositas pada Sample Berea di Routine Core Analysis Laboratorium BBPMGB “LEMIGAS” - Febriyana, Marine Chyntya; Welayaturromadhona (Journal of Sustainable Energy Development, 2024)
This study aims to analyze routine cores, especially for determining the porosity of a rock.  The samples tested by the coreval tool were 3 samples of 1.5 inch diameter with a length of 4.5 cm each. The sample used is a sample of Berea sandstone.  When the core sample comes, it is continued with ct-scan and spectral gamma ray. The next process is washing the fluid in the core sample. After cleaning from other fluids, the core sample will be dried in the oven. After it is completely dry, the sample must be stored in a desiccator containing silica gel. After ambient temperature, then the core sample is tested using Coreval 700.  The data inputted into the coreval computer are the name of the core sample, the dry weight of the core, the length of the core, and the diameter of the core. The coreval tool takes readings of bulk volume, pore volume, and porosity. This reading resulted in bulk volume values of 50.091 cc; 53.446 cc; and 52.410 cc, respectively. The pore volume value of each sample is 12.091 cc; 13.787 cc; and 13.385 cc. As for porosity, the value of each sample is 25.767%; 25.795%; and 25.540%. Keywords: coreval 700; permeability; porosity, RCAL